Grease: Rise of the Pink Ladies. Season one [videorecording (DVD)] - Oakes, Annabel; Tranter, Justin; Colbein, Brandon; Campbell, Brittany (Paramount, 2023)
Four outcast high school girls a brainiac student, a scandal-ridden cynic, a tomboy, and a fashion maven join together to form their own "girl gang" and trigger a rock-'n'-roll revolution at Rydell High. Of course, the adults are in a 1950s moral panic over the burgeoning new era, but the Pink Ladies are ready to get this party started.